Malay muslim youths of suburban areas : their tendency in electing political leaders - Azrie Azeh; Marzudi Md Yunus; Mohammad Tawfik Yaakob (Penerbit Universiti Kebangsaan Malaysia, 2023)
Islamic culture and political thought play an important role in Malaysia, a country whose official religion is Islam. The main objective of this study was to examine the level of Islamic political views among the Malay Muslim youths living in Malaysian suburban areas in electing political leaders. A quantitative method, using questionnaires as the research instrument, was employed in this study, which involved a total of 455 respondents, aged between 15 and 39 years old, from various backgrounds. The location of this study was in the Marang district, Terengganu. The study showed that most of the respondents (85.3%) agreed that it is very important for Islamic political values or characteristics to be practiced by political leaders. The findings also revealed that the Malay Muslim youths want a government that empowers the Islamic religion and safeguards the sovereignty of Islam and the nation